Modifikasi Nilai Luas Area dan Waktu Kunjungan Dalam Penghitungan Daya Dukung Kawasan Wisata di Provinsi Bali: Studi Kasus Pantai Geger - I Wayan Artadana; Abd. Rahman As-syakur; I Gusti Ngurah Putra Dirgayusa; Widiastuti Widiastuti (Journal of Marine and Aquatic Sciences, 2018)
Carrying Capacity is an important consideration in sustainable tourism development. One of the developing tourist destination in Bali island is Geger Beach which is located in Badung regency, Bali. Geger beach has different conditions with other beaches, therefore it is necessary to determine the estimation area and duration for tourist activities without degrading the quality of the environment. This study aimed to determine the unit of the area, the required time, and the total time per day for particular tourist category according to the condition at Geger beach. Moreover, this study investigated the condition of carrying capacity in the Geger beach. The data were collected primary data obtained by interviewed 100 respondents in Geger Beach and based on literature study on the secondary data. Results showed that the average area for tourism activities (Lt) is 41.5 m2 and the duration for tourism activities (Wp) is 2.29 hours/day. The total time that area provided for tourism activities is 10 hours/day and the total area is 5.023 m2. Carrying capacity value at Geger beach uses Lt and Wp value is 529 people/day, 16.385 people/month or 196.620 people/year. The carrying capacity of Geger Beach conditions is suggested remain under carrying capacity for the entire month and the total visits during 2016.